Reforestation in The Reclamation Area of Pongkor Gold Mining - Luluk Setyaningsih (Universitas Nusa Bangsa, 2023)
Ex-mining land is categorized as land with a high level of degradation. The loss of biodiversity, low soil fertility, loss of several layers of soil horizons, unbalanced texture, and even contamination can occur due to mining activities. Reforestation of mining land has been carried out with the approaches of improving the physical properties of the soil, selecting plant types, and improving soil biology in ex-gold mining land in Bogor. The addition of compost significantly increased organic matter content, C/N ratio, macronutrients (N, P, K) content, and improved soil texture. The application of Mycorrhiza and Rhizobium significantly increased the growth of forest plants such as trembesi (Samanea saman), gmelina (Anthocepalus cadamba), and ganitri (Elaeocarpus angustifolus) in ex-gold mining areas. Applying that significantly improved vegetation diversity on ex-gold mining land, including more than eight types of understory plants, and more than five plants were from the trees group. The result showed that reforestation of ex-mining land was feasible if it was carried out with a comprehensive approach.